Identification and Characterization of the CRISPR/Cas System in Staphylococcus aureus Strains From Diverse Sources - Cruz-López, Erick Adrian; Rivera, Gildardo; Cruz-Hernández, María Antonia; Martínez-Vázquez, Ana Verónica; Castro Escarpulli, Graciela; Flores-Magallón, Rebeca; Vázquez-Cisneros, Karina; Cruz-Pulido, Wendy Lizeth; Bocanegra-Garcia, Virgilio (Frontiers in Microbiology, 2021)
The CRISPR-Cas system provides defense mechanisms in bacteria and archaea versus mobile genetic elements, such as plasmids and bacteriophages, that can either be harmful or add sequences that can provide virulence or antibiotic resistance. Staphylococcus aureus is a gram-positive bacterium that could be the etiological agent of important soft tissue infections that can lead to bacteremia and sepsis. The role of the CRISPR-Cas system in S. aureus is not completely understood since there is a lack of knowledge about it. We analyzed 716 genomes and 1 genomic island from GENOMES-NCBI and ENA-EMBL searching for the CRISPR-Cas systems and their spacer sequences. Our bioinformatic analysis shows that only 0.83% (6/716) of the analyzed genomes harbored the CRISPR-Cas system, all of them were subtype III-A, which is characterized by the presence of the cas10/csm1 gene. Analysis of spacer sequences showed that 91% (40/44) had no match to annotated mobile genetic elements and 9% of spacer sequences corresponded to plasmids and bacteriophages; for instance, indicating that those phages had infected those S. aureus strains. Some of those phages have been proposed as an alternative therapy in biofilm-forming or infection with S. aureus strains, but these findings indicate that such antibiotic phage strategy would be ineffective. More research about the CRISPR/Cas system is necessary for a bigger number of S. aureus strains from different sources, so additional features can be studied.